The Effect of Pyrolysis Temperature and Amount of Zeolite Catalyst on Yield, Viscosity, and Cetane Index of Diesel Oil from LDPE Plastic Waste in The Process of Making Environmentally Friendly Diesel - Pieter, T. Yan Pieter Sianipar; Halimatuddahliana, H. (Golden Ratio of Social Science and Education, 2025)
Indonesia's rapid population growth and industrial development have increased fuel oil consumption, mainly diesel fuel. The high diesel fuel consumption is feared to cause the depletion of diesel fuel reserves. To overcome this problem, it is time for Indonesia to examine the use of alternative energy sources to replace diesel fuel. The raw material for alternative energy sources is plastic waste. The amount of plastic waste in Indonesia is relatively abundant, so it has potential when utilized as an alternative energy source through pyrolysis. This study aimed to analyze the effect of pyrolysis temperature and the amount of zeolite catalyst on the yield, viscosity, and cetane index of diesel oil from LDPE plastic waste that produces environmentally friendly diesel. The LDPE plastic waste used was 40 kg of crackle plastic. The pyrolysis temperatures were 250 C, 300 (o)C, 350 C, and 400 C. The amount of zeolite catalyst used was 0%, 2.5%, and 5%. The characteristics of diesel oil tested were viscosity and cetane index. The results were compared with the quality standards of diesel oil based on the Decree of the Director General of Oil and Gas No. 146 of 2020. The results showed that the highest yield of diesel oil was 6.83%, the best viscosity was 2.645 mm2/s, and the best cetane index was 51.61. The viscosity and cetane index of diesel oil that meets the quality standards of environmentally friendly diesel fuel based on the Decree of the Director General of Oil and Gas No. 146 of 2020 are found in diesel oil with pyrolysis temperatures of 300 C, 350 C, and 400 oC at 5% catalyst use, namely 2.334 mm(2)/s; 2.165 mm(2)/s; and 2.035 mm2/s for viscosity values and 47.13; 48.97; and 51.61 for cetane index values. The potential use of LDPE plastic waste as a diesel oil producer in North Sumatra Province in 2021 is 5,340 tonnes/year; by 2030, it will be 5,424 tonnes/year.